Implementation of a Fertilizer Quality Monitoring System for Planting Media Using an Android-Based 7-in-1 Soil Sensor - Rahmanita Fauziah; Ananda Lucky Pratama; Shita Fitria Nurjihan; Benny Nixon; Anik Tjandra Setiati; Dita Rahmadiani (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2026)
Fertilizer plays a crucial role in maintaining soil fertility and supporting optimal plant growth. However, fertilizer quality monitoring in previous studies has generally been conducted partially using separate tools and has not been integrated with an application-based real-time monitoring system, resulting in inefficiency and poor decision-making. This study aims to design and implement an integrated Android-based fertilizer quality monitoring system for planting media. The methods used include hardware design using a 7-in-1 soil sensor and an ESP32 microcontroller, Android-based software development, and data integration using the Firebase Realtime Database for real-time communication. System testing was conducted by measuring temperature, humidity, pH, and the content of Nitrogen (N), Phosphorus (P), and Potassium (K) in the planting media. The test results show that this system is capable of measuring parameters with a temperature value of 26.2°-28.7°C, humidity 25.3-29.1%, pH 6.2-7.1, nitrogen 107-250 ppm, phosphorus 280-478 ppm, and potassium 265-492 ppm in real-time. In addition, this system is equipped with an automatic fertilizer condition classification feature as well as plant recommendations and care suggestions. The main contribution of this research is the development of an Android-based fertilizer quality monitoring system that is integrated, real-time, and capable of increasing monitoring efficiency and supporting decision-making in sustainable planting media management.